Analisis Pengaruh Faktor Fundamental Terhadap Return Sahma (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2013-2017) - Endang Mahpudin; Ridha Annisa (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
This study aims to analyze the influence of Fundamental Factors consisting of Earning Per Share (EPS), Price to Earning Ratio (PER), Price to Book Value (PBV) and Dividend Payout Ratio (DPR) to Stock Returns both partially and simultaneously on Banking companies listed on the Indonesia Stock Exchange during the 2013-2017 period. Sampling was carried out using purposive sampling technique. The research method used is a quantitative method with descriptive and verification approaches. The results showed that partially there is significant influence from Price to Earning Ratio (PER) and Dividend Payout Ratio (DPR) to Return stock but there is no significant influence of the Earning Per Share (EPS) and Price to Book Value (PBV) of the Stock return . While the research results is simultaneously a significant influence on the Earning Per Share (EPS), Price to Earning Ratio (PER), Price to Book Value (PBV) and Dividend Payout Ratio (DPR) to Return stock.